A decade of the World Trade Organization and trade performance of Muslim countries - Mohd Amin, Ruzita (Association of Muslim Social Scientists, 2010)
The World Trade Organization (WTO), established on 1 January 1995 as a successor to the General Agreement on Tariffs and Trade (GATT), has played an important role in promoting global free trade. The implementation of its agreements, however, has not been smooth and easy. In fact this has been particularly difficult for developing countries, since they are expected to be on a level playing field with the developed countries. After more than a decade of existence, it is worth looking at the WTO's impact on developing countries, particularly Muslim countries. This paper focuses mainly on the performance ofmerchandise trade of Muslim countries after they joined the WTO. I first analyze their participation in world merchandise trade and highlight their trade characteristics in general. This is then followed by a short discussion on the implications of WTO agreements on Muslim countries and some recommendations on how to face this challenge.